2019
DOI: 10.1038/s41386-019-0440-6
|View full text |Cite
|
Sign up to set email alerts
|

Disconnection of drug-response and placebo-response in acute-phase antipsychotic drug trials on schizophrenia? Meta-regression analysis

Abstract: Differences in efficacy between antipsychotics and placebo in schizophrenia trials have decreased over the past decades. Previous studies have tried to identify potential explanatory factors focusing on response to placebo; however, it is still not clear which factors, if any, specifically moderate drug-response, as they may be different from those moderating placebo-response. Therefore, in this meta-regression analysis we explore whether there is an interaction between drug-response and placebo-response in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…Because ADHD is more frequently diagnosed and treated in the United States than in the rest of the world and research is also more prevalent in this country, expectations regarding the efficacy of pharmacological treatment may also be higher, resulting in higher placebo response. Nevertheless, it must be stressed that some studies on disorders other than ADHD have found placebo response to be lower in the United States ( Mallinckrodt et al, 2010 ; Welten et al, 2015 ; Leucht et al, 2018 , 2019 ), and other studies have found no effect of location on placebo response ( Bridge et al, 2009 ; Agid et al, 2013 ). Altogether, these results suggest that the true effect of location might be small or near zero and, for this reason, some studies find a positive, others a negative, and others a null effect.…”
Section: Discussionmentioning
confidence: 98%
“…Because ADHD is more frequently diagnosed and treated in the United States than in the rest of the world and research is also more prevalent in this country, expectations regarding the efficacy of pharmacological treatment may also be higher, resulting in higher placebo response. Nevertheless, it must be stressed that some studies on disorders other than ADHD have found placebo response to be lower in the United States ( Mallinckrodt et al, 2010 ; Welten et al, 2015 ; Leucht et al, 2018 , 2019 ), and other studies have found no effect of location on placebo response ( Bridge et al, 2009 ; Agid et al, 2013 ). Altogether, these results suggest that the true effect of location might be small or near zero and, for this reason, some studies find a positive, others a negative, and others a null effect.…”
Section: Discussionmentioning
confidence: 98%
“…Sample size and number of sites have been suggested as predictors of placebo response [ 50 , 51 , 92 ]. We also found that a larger sample size was associated with a larger placebo response in repetitive behaviors, yet the results might be driven by three antidepressant trials [ 65 – 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dependent variable was SMC and the independent variable was selected from a list of covariates from the literature [ 9 , 11 , 12 , 49 51 ]. First, we conducted univariable and then multivariable meta-regressions similar to our previous analyses in schizophrenia [ 51 ]: we used the factors that were significant in the univariable analysis and then a formal backward stepwise algorithm with a removal criterion of p = 0.15. Meta-regressions were not performed for categorical covariates with less than five data points per level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Continued trolled trials). A recent meta-regression analysis study reported differences in drug and placebo responses with the publication year, number of participants and sites, mean dose, minimum severity threshold as an inclusion criterion, chronicity, industry sponsorship, type of rating scale, diagnostic criteria, and number of medications [21]. The trials in the present study had some differences in patient characteristics and details of the study design.…”
Section: Discussionmentioning
confidence: 66%